Design and Implementation of an IoT-Based Smart Chicken Feeder System Using an ESP32 Microcontroller - M Yusfahmi; Nofri Wandi Al-Hafiz; Aprizal; Nacha Artha Hendrawan (Universitas Islam Kuantan Singingi, 2026)
Manual chicken feeding still faces various obstacles, such as inaccurate scheduling, dependence on the presence of farmers, and less than optimal monitoring of feed availability, which can affect the efficiency of farm management. This study aims to design and implement an Internet of Things (IoT)-based Smart Chicken Feeder system using an ESP32 microcontroller to automate chicken feeding and monitor feed availability in real-time. The research method uses a prototype approach that includes needs analysis, hardware and software design, implementation, and system testing. The hardware consists of an ESP32, a servo motor as an actuator to open and close the feed chute, an HC-SR04 ultrasonic sensor to detect feed height, and an IoT platform as a monitoring medium. Tests were conducted on the timeliness of feeding, sensor detection accuracy, actuator response, and internet communication stability. The test results show that the system is able to carry out automatic feeding according to schedule, detect feed conditions properly, and transmit monitoring information in real-time. The developed system can improve feed use efficiency, reduce errors due to human factors, and support the implementation of the smart farming concept in chicken farms.